Abu Jerami Dalam Kaca, Seramik Kaca Dan Komposit Polimer - Ismail, Hamisah (2010)
This work consists of three main parts; characterization of rice straw and rice straw ash, rice straw ash in glasses and glass ceramics, and rice straw ash as a filler in polymer composites. Rice straws were burnt at fix temperatures of 500, 700, 900 and 1050 oC, heating rate of 10oC/min, and soaking time of one hour. Tests that were carried included X-ray fluorescence (XRF), X-ray diffraction (XRD), differential thermal analysis/thermal gravimetry (DTA/TG), fourier transform infrared spectroscopy (FTIR) and field emission scanning electron microscopy (FESEM). A rice straw which is burnt at 1050 oC is found to have more silica content, which is 79 % in weight, compared to others temperature. Rice straw ash was used in glass making as a replacement for silica which is the main component in glass and normally resourced from silica sand. Three types of glasses produced, i.e AJ glass which used rice straw ash entirely as the silica source, AJPS glass used a mixture of 50 weight % of ash and 50 by % weight silica sand, and PS glass which were used silica sand entirely. Tests conducted on these three glasses were density and hardness tests. The parent glasses were analyzed by thermal analysis (DSC) to determine the nucleation and crystallization temperatures for subsequent heat treatment to produce glass ceramics. The tests for glass ceramics were density, hardness, XRD and also morphological analysis of the fracture surface.